Ideology, Politics, and Opinion Journalism: A Content Analysis of Spanish Online-Only Newspapers - Antonio Pineda; Núria Almiron (tripleC: Communication, Capitalism & Critique)
This study examines the ideological slant of Spanish digital-native opinion journalism. Political-ideological pluralism is a well-researched topic in media and journalism studies, yet there is less research regarding this topic when it comes to exclusively online media. This paper addresses that gap concerning the ways online-only opinion journalism can be defined in terms of their political ideology, and to what extent extreme ideological positions are represented in online journalism. Evidence from a content analysis of opinion columns appearing in the most widely-read Spanish online newspapers, during the month of May 2011 shows a general anti-left bias in the opinion sections of the newspapers , as well as a representation of the political extremes that is slightly more lenient with the far right. In line with Hallin and Mancini’s theory of polarized political news environments in countries like Spain, our results show that this polarization is characterized by a strong—but not always explicit—dominance of right-wing views.